Synthesis of the 2Fe subcluster of the [FeFe]-hydrogenase H cluster on the HydF scaffold - Shepard, Eric M. (National Academy of Sciences, 2010)
The organometallic H cluster at the active site of [FeFe]-hydrogenase consists of a 2Fe subcluster coordinated by cyanide, carbon monoxide, and a nonprotein dithiolate bridged to a [4Fe-4S] cluster via a cysteinate ligand. Biosynthesis of this cluster requires three accessory proteins, two of which (HydE and HydG) are radical S-adenosylmethionine enzymes. The third, HydF, is a GTPase. We present here spectroscopic and kinetic studies of HydF that afford fundamental new insights into the mechanism of H-cluster assembly. Electron paramagnetic spectroscopy reveals that HydF binds both [4Fe-4S] and [2Fe-2S] clusters; however, when HydF is expressed in the presence of HydE and HydG (HydF(EG)), only the [4Fe-4S] cluster is observed by EPR. Insight into the fate of the [2Fe-2S] cluster harbored by HydF is provided by FTIR, which shows the presence of carbon monoxide and cyanide ligands in HydF(EG). The thorough kinetic characterization of the GTPase activity of HydF shows that activity can be gated by monovalent cations and further suggests that GTPase activity is associated with synthesis of the 2Fe subcluster precursor on HydF, rather than with transfer of the assembled precursor to hydrogenase. Interestingly, we show that whereas the GTPase activity is independent of the presence of the FeS clusters on HydF, GTP perturbs the EPR spectra of the clusters, suggesting communication between the GTP- and cluster-binding sites. Together, the results indicate that the 2Fe subcluster of the H cluster is synthesized on HydF from a [2Fe-2S] cluster framework in a process requiring HydE, HydG, and GTP.